Bend: Immutability and Native Parallelism as a Solution to Parallel Programming Challenges - Barros, Ramon C. Jales de; Souza, Samuel Xavier de (Anais do Workshop em Engenharia de Software para Programação Funcional (SE4FP), 2025)
With the physical limits of modern processors, parallel programming has become essential to fully harness the potential of current architectures. However, challenges such as race conditions and deadlocks increase the complexity of parallel development. Bend, a functional language with native parallelism, proposes an immutability-based approach to simplify this process. This article analyzes how immutability and native parallelism in Bend eliminate shared memory conflicts, enabling safe and effortless parallelism without explicit synchronization. Through a case study involving tree summation, we compare Bend with a mutable approach in C.